PENGUATAN KESADARAN GIZI ANAK SEKOLAH DASAR MELALUI PENYULUHAN SAYUR DAN BUAH SEBAGAI PRAKTIK PENDIDIKAN SOSIAL DI KECAMATAN GANGGA - Zulhakim, Zulhakim; Ismi, Azizatul (Hudan Lin Naas: Jurnal Ilmu Sosial dan Humaniora, 2025)
Good nutritional awareness in school-age children is very important to support optimal growth and development. However, the low consumption of vegetables and fruits among elementary school students is a problem that requires educational intervention. This study aims to analyze the effectiveness of vegetable and fruit consumption counseling in increasing nutritional awareness of elementary school students in Gangga District, North Lombok Regency. The method used is quantitative research with a quasi-experiment design using a pre-test and post-test control group approach. Counseling was carried out in the form of lectures with four-minute video media. The research sample consisted of 60 students who were divided into an experimental group and a control group. Data analysis was carried out using the Wilcoxon test to see changes in knowledge and attitude scores before and after counseling. The results showed that there was a significant improvement in students' knowledge and attitudes in the experimental group after being given counseling. The knowledge score increased from 43.00 to 75.00 (p=0.000), while the attitude score increased from 45.33 to 72.60 (p=0.000). On the other hand, in the control group that was not given counseling, there was a decrease in knowledge scores from 44.00 to 38.00 (p=0.039) and attitude scores experienced a slight increase from 41.00 to 42.66 (p=0.059), which was not significant. These findings indicate that without educational intervention, students' nutritional awareness tends to decline or remain stagnant. This study confirms that lecture-based counseling and audiovisual media are effective in increasing nutritional awareness of elementary school students. Therefore, nutrition education programs should be integrated into the school curriculum and supported by policies that encourage the consumption of vegetables and fruits from an early age. Further research is suggested to cover a wider range and use more diverse intervention methods.